Synthesis of a hexahydropyrrolo indole (HPI) compound library. Issue 11 (1st June 2015) - Nickel, Sabrina; Nickel, Philipp; Hellmert, Marco; Ernst, Silvia; Jewell, Robert; Pearce, Christopher A.; Jones, Geraint; Hamza, Daniel; Kaiser, Markus
Graphical abstract: Abstract: Scaffolds of natural products represent promising starting points for the development of focused compound libraries. Here, we describe the development of a synthetic route to a compound library based on the hexahydropyrrolo indole (HPI) scaffold, the denoting structural motif of the HPI natural product family. To this end, a two-step approach consisting of a batch synthesis of an advanced functionalizable HPI intermediate followed by the establishment of reaction conditions that allow derivatization of this scaffold at three different positions is described. Subsequently, the optimized methods were applied to the synthesis of a 276-member library.